Pelvic congenital arteriovenous malformation diagnosed by transrectal ultrasonography: A case report - Suzuki, Kenjiro; Tanaka, Nobuyuki; Ebine, Takashi; Momma, Tetsuo (Canadian Urological Association Journal, 2012)
Arteriovenous malformations (AVMs) of the pelvis are relatively rare and difficult to treat because of multiple and extensive feeding vessels. We report the case of a 69-year-old male with pelvic congenital AVM that was detected during tests for dysuria. He visited our hospital complaining of voiding difficulty. Digital rectal examination revealed a pulsating mass that was palpable on the right side of the prostate. Transrectal ultrasonography showed multiple hypoechoic lesions adjacent to the prostate and colour Doppler ultrasonography revealed the flow regions corresponded to the hypoechoic lesions. Computed tomography demonstrated large-to-small tubular vessels adjacent to the prostate, while pelvic angiography showed many small feeder arteries extending mainly from the right internal iliac artery. He was diagnosed as having pelvic congenital AVM. Uroflowmetry revealed slight voiding difficulty without residual urine. The patient decided against treatment and requested we monitor his clinical course.